Gabonius gen. nov. (Leguminosae, Caesalpinioideae, Detarieae), a distant cousin of Hymenostegia endemic to Gabon - Wieringa, Jan J.; Mackinder, Barbara A.; van Proosdij, André S.j. (Phytotaxa, 2013)
A new genus, Gabonius is described to accommodate a single species, Gabonius ngouniensis which was previously misplaced in Hymenostegia sensu lato. Gabonius ngouniensis is a widespread Gabonese endemic of evergreen forest. We assess G. ngouniensis as Least Concern (LC) according to IUCN criteria. A distribution map of Gabonius is presented, as is a table comparing the morphology of Gabonius, the closely related, possibly sister genus Micklethwaitia and Hymenostegia sensu stricto from which G. ngouniensis has been excluded. The previously unreported seedling morphology is discussed.